Faktor penyebab kesulitan pembelajaran matematika - Yoga, M. Rafi Prima (Maliki Interdisciplinary Journal, 2025)
This study aims to identify the factors influencing learning difficulties in mathematics among students using a comparative analysis method. The analyzed factors are divided into two categories that is internal factors and external factors. Internal factors include physical health, physical disabilities, the perception that mathematics is difficult, lack of student motivation, low conceptual understanding, and lack of concentration. Meanwhile, external factors encompass insufficient parental attention to children’s learning, family atmosphere at home, community activities, the use of learning media, and the influence of mass media. The results indicate that the combination of these factors significantly contributes to students’ difficulties in understanding mathematical concepts. Therefore, collaborative efforts between teachers, parents, and students are necessary to create a better learning environment.